Recruitment and Selection Process Effect on Employee Performance at PT. Bumi Sarana Utama Kalla Aspal Branch Sorong - Muh. Reza Nuzul Ramadhan; Susetyowati Sofia; Digor Mufti (www.amertainstitute.com, 2025)
This study aims to determine the effect of the recruitment and selection process on employee performance at PT. Bumi Sarana Utama Kalla Aspal Branch Sorong. Recruitment and selection are crucial component in human resource management that significantly influence organizational effectiveness. The research employs a quantitative approach with data collected from 30 respondents using questionnaires. The data analysis method used is multiple linear regression. The findings indicate that both recruitment and selection processes have a significant positive effect on employee performance. The result suggest that improving the recruitment and selection mechanisms can lead to enhanced employee performance. The study is expected to contribute to the understanding and implementation of more effective human resource practices.